Neuroinflammation in Temporal Lobe Epilepsy Measured Using Positron Emission Tomographic Imaging of Translocator Protein - Gershen, Leah D; Zanotti-Fregonara, Paolo; Dustin, Irene H; Liow, Jeih-San; Hirvonen, Jussi; Kreisl, William C; Jenko, Kimberly J; Inati, Sara K; Fujita, Masahiro; Morse, Cheryl L; Brouwer, Chad; Hong, Jinsoo S; et al. (JAMA neurology, 2015)
Neuroinflammation may play a role in epilepsy. Translocator protein 18 kDa (TSPO), a biomarker of neuroinflammation, is overexpressed on activated microglia and reactive astrocytes. A preliminary positron emission tomographic (PET) imaging study using carbon 11 ([11C])-labeled PBR28 in patients with temporal lobe epilepsy (TLE) found increased TSPO ipsilateral to seizure foci. Full quantitation of TSPO in vivo is needed to detect widespread inflammation in the epileptic brain. To determine whether patients with TLE have widespread TSPO overexpression using [11C]PBR28 PET imaging, and to replicate relative ipsilateral TSPO increases in patients with TLE using [11C]PBR28 and another TSPO radioligand, [11C]DPA-713. In a cohort study from March 2009 through September 2013 at the Clinical Epilepsy Section of the National Institute of Neurological Disorders and Stroke, participants underwent brain PET and a subset had concurrent arterial sampling. Twenty-three patients with TLE and 11 age-matched controls were scanned with [11C]PBR28, and 8 patients and 7 controls were scanned with [11C]DPA-713. Patients with TLE had unilateral temporal seizure foci based on ictal electroencephalography and structural magnetic resonance imaging. Participants with homozygous low-affinity TSPO binding were excluded. The [11C]PBR28 distribution volume (VT) corrected for free fraction (fP) was measured in patients with TLE and controls using FreeSurfer software and T1-weighted magnetic resonance imaging for anatomical localization of bilateral temporal and extratemporal regions. Side-to-side asymmetry in patients with TLE was calculated as the ratio of ipsilateral to contralateral [11C]PBR28 and [11C]DPA-713 standardized uptake values from temporal regions. The [11C]PBR28 VT to fp ratio was higher in patients with TLE than in controls for all ipsilateral temporal regions (27%-42%; P < .05) and in contralateral hippocampus, amygdala, and temporal pole (approximately 30%-32%; P < .05). Individually, 12 patients, 10 with mesial temporal sclerosis, had asymmetrically increased hippocampal [11C]PBR28 uptake exceeding the 95% confidence interval of the controls. Binding of [11C]PBR28 was increased significantly in thalamus. Relative [11C]PBR28 and [11C]DPA-713 uptakes were higher ipsilateral than contralateral to seizure foci in patients with TLE ([11C]PBR28: 2%-6%; [11C]DPA-713: 4%-9%). Asymmetry of [11C]DPA-713 was greater than that of [11C]PBR28 (F = 29.4; P = .001). Binding of TSPO is increased both ipsilateral and contralateral to seizure foci in patients with TLE, suggesting ongoing inflammation. Anti-inflammatory therapy may play a role in treating drug-resistant epilepsy.